LICOS, a primordial costimulatory ligand? - Brodie, D; Collins, A; Iaboni, A; Fennelly, J; Sparks, L; Xu, X; Van Der Merwe, P; Davis, S (2000)
In mammals, the classical B7 molecules expressed on antigen-presenting cells, B7-1 (CD80) and B7-2 (CD86), bind the structurally related glycoproteins CD28 and CTLA-4 (CD152), generating costimulatory signals that regulate the activation state of T cells. A recently identified human CD28-like protein, ICOS, also induces costimulatory signals in T cells when crosslinked with antibodies, but it is unclear whether ICOS is part of a B7-mediated regulatory pathway of previously unsuspected complexity, or whether it functions independently and in parallel. Here, we report that, rather than binding B7-1 or B7-2, ICOS binds a new B7-related molecule of previously unknown function that we call LICOS (for ligand of ICOS). At 37 degrees C, LICOS binds only to ICOS but, at lower, non-physiological temperatures, it also binds weakly to CD28 and CTLA-4. Sequence comparisons suggest that LICOS is the homologue of a molecule expressed by avian macrophages and of a murine protein whose expression is induced in non-lymphoid organs by tumour necrosis factor alpha (TNFalpha). Our results define the components of a distinct and novel costimulatory pathway and raise the possibility that LICOS, rather than B7-1 or B7-2, is the contemporary homologue of a primordial vertebrate costimulatory ligand.